2020
DOI: 10.1111/bjh.16769
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia as an initial manifestation of COVID‐19; case series and literature review

Abstract: COVID-19 has been declared as a global pandemic, affecting more than a hundred countries in a matter of weeks and claiming many lives up until now. The clinical spectrum ranges from asymptomatic carriers to symptomatic patients with mild symptoms and patients requiring intensive care unit (ICU) admission at the other extreme. Variable clinical presentations have been reported, most commonly involving the chest with shortness of breath being most common. Less commonly it has also been reported with gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…U.S. hospitals have reported lower proportions of intubated critically ill pediatric COVID-19 patients and fewer ventilated days (8,9). Thrombocytopenia was associated with critical illness and has been described as an early finding in patients with COVID-19 (10). Thrombocytopenia is suspected to be multifactorial and could be due to cytokine storm or direct effects of SARS-CoV-2 on bone marrow, host immunity, or lung parenchyma (11).…”
Section: Discussionmentioning
confidence: 99%
“…U.S. hospitals have reported lower proportions of intubated critically ill pediatric COVID-19 patients and fewer ventilated days (8,9). Thrombocytopenia was associated with critical illness and has been described as an early finding in patients with COVID-19 (10). Thrombocytopenia is suspected to be multifactorial and could be due to cytokine storm or direct effects of SARS-CoV-2 on bone marrow, host immunity, or lung parenchyma (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the study population, 26 patients had complete response and 8 patients showed only response to treatment according to study definition. A total of 3 individuals expired: one was due to intracranial hemorrhage [11] and others succumbed to severity of COVID-19 illness after showing platelet response to treatment [15,27]. A total of 4 patients (9%) had relapse following treatment response in the followup period [13,14].…”
Section: Treatment and Clinical Outcomesmentioning
confidence: 99%
“…In two patients, the microhemorrhage in ventricles or subarachnoid space was not life-threatening. Non-ICH severe forms of bleeding, such as gastrointestinal bleed, metrorrhagia, and hematuria, were reported in 7 patients [11,14,15,18,25,29]. Severe forms of bleeding at ITP onset were found to be rare (< 1%) in a large population-based study comprising 3771 incident ITP patients [52].…”
Section: Profile Of Patients With Covid-19-associated Itpmentioning
confidence: 99%
“…The other previously reported cases had also heterogeneous presentations (different phases of COVID-19 and severity) and several treatments and results [2][3][4][5][6][7][8][9]. Twelve out of 14 were treated with Immunoglobulin, five additionally with corticosteroids and two received platelet transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported to be associated with a different coronavirus strain [1]. Recently a number of cases of ITP have been reported associated with SARS-CoV-2 [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%